The role of public expenditure in achieving economic growth in Algeria Analytical study for the period (2000-2017) - Guerroumi, Hamid; Benlecheb, Hamza (Milev Journal of Research and Studies, 2018)
This research aims at identifying the role of public expenditure in achieving economic growth in Algeria during the period 2000-2017. This is done by addressing the theoretical framework of public expenditure as well as economic growth. The analytical approach is shown in the practical aspect through the analytical study of public expenditures and economic growth rates in Algeria during the period of study, based on figures and data. The study concluded that despite the expansive expansion policy pursued by the Algerian government since the beginning of the third millennium through the adoption of development programs that sought to achieve the objectives of the most important growth rates outside the hydrocarbons sector and diversification of the economy and the elimination of excessive dependence on fuel, but the results remain modest, The current oil crisis has shown us the fragility of the Algerian economy and its growth rates in the hydrocarbon sector, which necessitates accelerating the development of an integrated program to develop and build a diversified and productive economy.